The Owl & the Nightingale: Musical Life and Ideas in France 1100-1300 - Page, Christopher 1952- (London Dent, 1989)
Music and literature enjoyed a renaissance in the twelfth and thirteenth centuries. That period witnessed, among other things, the rise of the troubadours and trouveres, the elaboration of Notre Dame polyphony, and the emergence of Romance. Everywhere a new, secular spirit was coming into conflict with the older, more severe view of man and his music. It was the age of the debate between the owl and the nightingale, so called after a Middle English poem that pits the owl (the traditional asceticism of Christianity) against the nightingale (the new, more joyous and humane, social and intellectual trends of the times). Christopher Page, one of the most original music historians, examines this continuing struggle as it was fought by monks, preachers, commentators, and many others in the great and clamorous aviary of the Christian Church. Drawing upon an astonishing range of literary evidence, much of it from rare manuscripts, he enables us to see the musical life as well as the literature of the twelfth and thirteenth centuries in a new light.A hardback book in very good condition with some shelf wear, one notable tear at the top of the cover.
Keywords: Middle Ages (500-1400); Music history; France